นโยบายของไทยต่อปัญหากัมพูชา : ศึกษาทัศนะของผู้นำไทยต่อภัยคุกคามของเวียดนาม พ.ศ. 2522-2532 - ฉัตริยา วิสุทธิวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
This thesis studies the perception of Thai leaders that influence the Thai policy toward the Kampuchean problems (1979-1989), by conceptualizing the perception in the framework of "threat perception". According to the study, Thai policies toward the Kampuchea problems have two phases. The first phase is in the era of Kriengsak Chamanund’s government and the Prem Tinsulanonda’s government. Thai policies were security-oriented, omni-directional, anti the Vietnamese and the Heng Samrin’s governments, and comprehensive solutions by political and diplomatic means. These policies derived from Thai leaders’ perception on Vietnam as a threat to Thai security and regional stability. The factors that influence Thai leaders’ perceptions were the intent of Vietnam forming an Indochinese Federation, the roles of the Vietnamese Communist Party, the Vietnamese invasion of Kampuchea, the Vietnamese military incursion into Thai territory and an anxiety of Thai leaders about the potential of Vietnamese army. The second phase which was in the Chatichai Choonhavan’s government era, is the turning point of Thai policies toward the Kampuchean problems as it was displayed the changing of "the battle field into the market place policy" , the open-door policy toward the Vietnamese and the Heng Samrin’s governments, and the "step by step" economic solution. As Chatichai’s thought that they should separate economic from political issues. Moreover, due to the withdrawal of Vietnamese troop from Kampuchea, the Chatichai perceived that Vietnam was no longer a threat to Thailand. Finally, the background of the three Thai leaders’ and international environments were also important factors for the shaping of Thai leaders’ perception.